The Influence of Loop Length on Microcapsule Loading Capability of Interlock Knitted Fabric - Dao, Thi Chinh Thuy; Chu, Dieu Huong (Old Journal, 2017)
Microcapsule application is a modern method of finishing functional textiles. Microcapsule loading capability of fabric, a very important value for evaluating the efficiency of this method, depends on many factors including fabric structural parameters. In this study, the influence of loop length on microcapsule loading capability of Interlock knitted fabrics was investigated. Eudragit RSPO microcapsules containing Ibuprofen were made by solvent evaporation method. Five levels of loop length on Cotton Interlock knitted fabric were 2.81, 2.83, 2.87, 2.96, 3.05 mm and three levels of this on CVC 60/40 Interlock knitted fabric were 2.65, 2.80, 2.95 mm (both series of fabrics had yarn count of Ne40/1). Microcapsules were impregnated onto fabric by wet coating. Microcapsule loading capability of fabric was determined by the change in mass of fabric after microcapsule impregnation. The regression equation expressing the influence of loop length on microcapsule loading capability was approached by least squares method. The results showed that for both series of fabrics, microcapsule loading capability depended on loop length by a quadratic function with high coefficient of determination (0.9÷1).